Electrodynamic Characteristics of Multilayered System of Plane Screens with a Slot - Kaliberda, M.E.; Lytvynenko, L.M.; Pogarsky, S.A. (Радиофизика и радиоастрономия, 2011)
The diffraction by a finite and semi-infinite system of plane screens with a slot is considered. The problem is solved with the operator approach. The possibility of screens shift in the plane of their displacement is taken into consideration